CONTEMPORARY THEOLOGICAL ISSUES IN URBAN SOCIETY: A REVIEW OF QASIM MATHAR'S ISLAMIC THOUGHT AND HIS CONTRIBUTION TO BUILDING THEOLOGICAL AWARENESS IN MAKASSAR, SOUTH SULAWESI - Barsihannor, Barsihannor; Tahir, Gustia; Ilham, M.; Nasiha, Irenna (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
Due to the rapid development of information technology, the world is increasingly open. This causes the people of the world be intensely connected to each other. The diversity of cultures, beliefs, and religious practices is becoming more open. If society is not educated about the importance of diversity awareness, then conflict can occur. This study discusses the thoughts of Moh. Qasim Mathar on contemporary theological issues and his contribution to building theological awareness in the city of Makassar. The data collection method was carried out through an in-depth study of his thoughts (content analysis) which were published periodically in the mass media through the Jendela Langit column in the Fajar Newspaper, as well as through in-depth interviews with a number of sources. The results of the study confirm that Qasim Mathar offers valuable insights into the importance of building an inclusive theology and maintaining pluralism in the midst of urban society to ensure the presence of harmony and coexistence of pluralistic, heterogeneous, and dynamic urban society. This study also reveals how Qasim Mathar's thoughts contribute to presenting theological awareness in the midst of urban society. The presence of religious dialogue spaces in several institutions such as in MUI, Postgraduate Program, Cadar Garis Lucu Community, House of Philosophy, and Matahari Islamic Boarding School Foundation is the real evidence of Qasim Mathar's contribution to urban society. The findings of this study indicate that Mathar's thoughts provide a framework for understanding the flexibility and resilience of theology in facing modern challenges, and highlight the importance of contextualizing religious values in the socio-cultural realities of urban society.